The effectiveness of the Multisensory Method on Early Reading Ability in 6-7 Years Old Children - Zulhendri Zulhendri; Jhoni Warmansyah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2021)
Early reading is an important primary capital that students have in conducting their academic knowledge, but there are still many elementary school students who have not mastered the skills. Using the right reading method can support children's skills in reading. The purpose of the study is to determine the effectiveness of the Multisensory method on the early reading skills in 6-7 years old children of the State Elementary School 10 Ganting Bigau and the State Elementary School 19 Koto Tuo, the Sulit Air Village, District X Koto diatas, the Regency of Solok. Withdrawal of samples with simple random sampling technique. Data collection is conducted by adapting instruments from ERSI (The Early Reading Screening Instrument). The data analysis technique is an independent T-test that is to see a comparison of differences in the average score. The results showed that the Multisensory method was effective in developing early reading skills in Grade 1 students at elementary school. The use of multisensory reading methods can be an alternative to the choice of reading by the teacher in improving the student's initial reading.